F.LES : tentoonstellingsproject. - Andrea, Carole; Boons, Anne; Brutin, Hugo; Carbonnet, Muriel; Gaalman, Annette; Hjg; Hérissé, Marc; Simonelli, Jacques; Van Gorp, Carine; Varga, Marek; Wille, Jonas (Overijse : BKO Kunstschool, 2000)
Callens, Mario ; Boons, Anne ; van Maele, Marcel ; Lodewijckx, Renée ; Oeil, Mon ; Gonissen, Willo ; Custers, Lucas Pellens & Stefan ; Backus, Pi ; Kuijs, Hans ; Veerman, Elsbeth ; Van Gorp, Carine ; Bleus, Guy ; Devens, Dré ; Chabot, Andre ; Giai-Miniet, Marc ; Dessons, Pierre ; Chenu, Didier ; Marcoville ; Coville, Jacky ; Mas, Jean ; Moya, Patrick ; Leung, Yiu Wah ; Lin, Man-Chi ; Chiang, Ju-Hai ; Webster, Gary
biografie
F.LES : tentoonstellingsproject, BKO Kunstschool, Overijse, 2000
Nederlands & Frans & Engels
boek